2018
DOI: 10.1557/adv.2018.119
|View full text |Cite
|
Sign up to set email alerts
|

Possible superconductivity in Bismuth (111) bilayers. Their electronic and vibrational properties from first principles

Abstract: Using a 72-atom supercell we report ab initio calculations of the electronic and vibrational densities of states for the bismuth (111) bilayers (bismuthene) with periodic boundary conditions and a vacuum of 5 Å, 10 Å and 20 Å. We find that the electronic density of states shows a metallic character at the Fermi level and that the vibrational density of states manifests the expected gap due to the layers. Our results indicate that a vacuum down to 5 Å does not affect the electronic and vibrational structures no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…A year after our prediction, experimentalists proved us correct and they found that the Wyckoff structure superconducts below 0.53 mK at ambient pressure [9]. We had ventured to estimate superconducting temperatures for bismuth under various conditions; for the crystalline phase, that had not been found to superconduct, we succeeded; our other predictions await verification [7,10]. So, with this succinct background we decided that bismuth was the ideal "guinea pig" to test the effect of negative pressures and we undertook the search to see if it could become metallic or a semiconductor under expansion, and what the possibilities were to find it in a superconducting state.…”
Section: Introductionmentioning
confidence: 70%
“…A year after our prediction, experimentalists proved us correct and they found that the Wyckoff structure superconducts below 0.53 mK at ambient pressure [9]. We had ventured to estimate superconducting temperatures for bismuth under various conditions; for the crystalline phase, that had not been found to superconduct, we succeeded; our other predictions await verification [7,10]. So, with this succinct background we decided that bismuth was the ideal "guinea pig" to test the effect of negative pressures and we undertook the search to see if it could become metallic or a semiconductor under expansion, and what the possibilities were to find it in a superconducting state.…”
Section: Introductionmentioning
confidence: 70%
“…Finally, the equations we shall use for the Γ phase are Tc Γ = {Tc W } 1/ η δ {1.13 θD W } ( η-1) / η , (5) where we have explicitly included the Wyckoff phase as the reference phase. Also, N(EF) Γ = η N(EF) W , (6) and…”
Section: The Methodsmentioning
confidence: 99%
“…However, it is possible to obtain results like the ones reported in this work that give an indication as to what materials may become superconductors if the N(E) and the F(ω) are known, and if the Cooper attraction sets in. In what follows we shall recur to some of our previous publications [3,[5][6][7] since the procedure is the same for these series of calculations.…”
Section: Procedure: the Bcs Approachmentioning
confidence: 99%
See 2 more Smart Citations